σ-Centralizers of triangular algebras - Ashraf, M.; Ansari, M. A. (Ukrains’kyi Matematychnyi Zhurnal, 2023)
UDC 512.5 In this paper, we characterize Lie (Jordan) σ-centralizers of triangular algebras. More precisely, we prove that, under certain conditions, every Lie σ-centralizer of a triangular algebra can be represented as the sum of a σ-centralizer and a central-valued mapping. Further, it is shown that every Jordan σ-centralizer of a triangular algebra is a σ-centralizer.